Jornalismo e sociedade: a (in) visibilidade do idoso na imprensa - Campos, Pedro Celso [UNESP]; Fontes, Camila Sayuri Kurashima [UNESP]; Meassi, Carla Grandelli [UNESP]; Monteiro, Daniela Penha [UNESP]; Morais, Camila Franco [UNESP]; Nascimento, Gabriela Fernanda [UNESP]; Piola, Bruno César Tozatti [UNESP]; Sei, Marisa Naomi [UNESP] (My University, 2011)
This article intends to inventory the medias that also cover Third Age in Brazil, in view of that all the demographic pointers reveal the accented process of aging of the world-wide population, and therefore of our country. A time that the journalists cannot ignore the changes that occur in the interior of the society, in which it is the main area of performance of the journalism, we want to understand why the Brazilian media still dedicates so little space to this phenomenon of the elderly, in contrast of what occurs in other countries. We ask ourselves, then, if the change in the way of looking at the elderly one would not have to be born inside of the University, through the young who prepare for the exercise of the profession, with citizenship and social concern. In the Course of Journalism of the UNESP/Bauru a group of future journalists is searching this subject, for this they sign this article.

Este artigo pretende inventariar os meios de comunicação que cobrem Terceira Idade no Brasil, tendo em vista que todos os indicadores demográficos revelam o acentuado processo de envelhecimento da população mundial, portanto também de nosso país. Uma vez que os jornalistas não podem ignorar nas mudanças que ocorrem no interior da sociedade, na qual está a principal área de atuação do jornalismo, queremos compreender por que a mídia brasileira ainda dedica tão pouco espaço a esse fenômeno do envelhecimento, ao contrário do que ocorre em outros países. Perguntamo-nos, então, se a mudança no modo de olhar o idoso não deveria nascer dentro da Universidade, através dos jovens que se preparam para o exercício da profissão, com cidadania e preocupação social. No Curso de Jornalismo da UNESP/Bauru um grupo de futuros jornalistas está pesquisando este assunto, por isto assinam este artigo.
Keywords: Journalism; Elderly; Citizenship; Jornalismo; Idoso; Cidadania